Estimación de polimorfismos del gen de leptina bovino en poblaciones de las razas criollas Hartón del Valle, Blanco Orejinegro (BON) y en la raza Brahman (2005)
ABSTRACT: Recent investigations have identified some regions between and adjacent to the leptin gene, associated with different carcass fat levels in bovines in wich frequencies vary greatly from one race to another, and from one population to another. This investigation determined the polymorphisms for the region 5 UTR and flanking region to the end 3’ of the leptin gene using two markers ST and WD (G18586 and U50365). 261 animals were evaluated of Hartón del Valle (100), Brahman (121) and BON (40) cattle. Were evaluated the result of this analysis where, 7 different alelles for microsatellite ST and 15 for WD, in the total population. The creole populations evaluated for marker ST are not in Hardy-Weinberg (HW) equilibrium. The marker WD only appeared H-W equilibrium for the population Brahman. The Brahman cattle was the most polymorphic cattle for microsatellites ST, where 6 for ST alleles were found. For WD the most polymorphic cattle was Hartón del Valle and less polymorphic cattle was the BON, with 6 for ST and 6 for WD alleles.